Entre gênero, feminismo e utopia: as reconfigurações da maternidade em narrativas de Marge Piercy e Octavia Butler - Prado, Amanda Priscila Santos (2013)
The present study is focused on the discussion and analysis of the ways in which the novel Woman on the Edge of Time (1977), by Marge Piercy, and the short story "Bloodchild" (1984), by Octavia E. Butler, reconfigure traditional notions of motherhood from alternative positions, weaving approaches between the fictions focused and some critical trends in feminist political thought. To his end, this study initially presents reflections on the interfaces between motherhood, gender and representation, based on theories by Simone de Beauvoir (1949), Adrienne Rich (1979), Elizabeth Badinter (1985; 2011), Susana Funck (1998) Nancy Chodorow (2002), Cristina Stevens (2006; 2007), Susan H. Lees (1984) and Judith Butler (1987). These reflections function to contextualize the readings of Marge Piercy’s and Octavia E. Butler’s narratives which are also informed by theorizing about the qualities of literary representation (ISER, 2002; ECO, 2010), about parody (HUTCHEON, 1985; 1991) and about literary genres (TODOROV, 2010). By privileging an interdisciplinary reading approach, the study also incorporates texts from cultural spheres other than literary, whose themes relate to motherhood, such as: abortion (DINIZ, 2012), desire for children (DINIZ, 2012) and madness (MARIZ, 2012). In general, the readings offered indicate a destabilization of crystallized notions of gender in culture engendered by the reconfiguration of notions of motherhood observed in the Marge Piercy’s and Octavia E. Butler’s fictions. Such reconfigurations were analyzed from two perspectives: the first one, through an interdisciplinary analytical approach that focuses on questions related to contemporary gender relations; and the second, by analyzing the way the story provokes a rupture in relation to some genres of literary culture by means of a parody to such gender relations as represented in traditional literary forms.